Espetáculo “BR trans”: micropolíticas, performances e cartografias queer - Costa, José Carlos Lima (2018)
The present research intends to analyze the play "BR Trans", taking as base the performances and the performativities that emerge from its. I took the notion of performance in Butler as the guiding thread of the current research, which disarticulates the process of materialization and normalization of bodies by demonstrating that the gender is a repetition of stylized acts. I read "Trans BR" as a political, revolutionary manifesto because it manifests an action; it is a “war machine” against the exclusionary standards, based on the silencing of differences. “BR Trans” brings together narratives from the relations that Silvero Pereira established with the trans universe. Therefore, to think the play in analysis is to disassemble the current theatrical thought, proposing a Queer Theater, that is, a micropolitical, aesthetic and artistic agency that devours the structures of contemporary theater and proposes a new scene that, in fact, is a way of life activist, because it no longer seeks to move away from life, but life itself is taking shape in each scene. As a perspective of analysis, I adopted cartography, a method attributed to Deleuze and Guattari, and that it is a way of thinking that puts in check the norms, the notion of subject, roots and the image-tree of the world. In cartography, binarisms deconstructed are, because it operates through the rhizome, not the representation or decal of the world. It is a look that bets on thinking in transit, displacing and deterritorializing ways of thinking and living, and drag us to new processes of subjectivation. The emergence of post-structuralism and post-Nietzsche's nomadic thoughts, such as Foucault, Deleuze, and Guattari, and post-identities such as Butler's, made it possible to think of theater, especially theater, as art traversed by social issues such as a “war machine” against the devices that try to adapt the subjects to the established binarisms.